Copper-and-Nitrogen-Codoped Zirconium Titanate (Cu-N-ZrTiO4) as a Photocatalyst for Photo-Degradation of Methylene Blue under Visible-Light Irradiation - Lenny Rahmawati; Rian Kurniawan; Niko Prasetyo; Sri Sudiono; Akhmad Syoufian (Indonesian Journal of Chemistry, 2023)
Synthesis and characterization of copper-and-nitrogen-codoped zirconium titanate (Cu-N-ZrTiO4) as a photocatalyst for the degradation of methylene blue (MB) have been conducted. The main purpose of this research was to investigate the co-doping effect of copper and nitrogen dopants in ZrTiO4 as a photocatalyst for the photodegradation of MB. Titanium-(IV) tetraisopropoxide (TTIP) was dissolved into ethanol and mixed with aqueous zirconia (ZrO2) suspension containing 10% nitrogen (N) (w/w to Ti) from urea and various amount of copper as dopants. The calcination was performed at temperatures of 500, 700, and 900 °C. The composites were characterized using Fourier transform infrared spectrophotometer (FTIR), X-ray diffractometer (XRD), scanning electron microscopy with energy dispersive X-ray (SEM-EDX) mapping, and specular reflectance UV-Visible spectrophotometer (SRUV-Vis). The degradation of 4 mg L−1 MB solution was conducted for various irradiation times. Characterization shows a significant decrease of the ZrTiO4 band gap from 3.09 to 2.65 eV, which was given by the composite with the addition of 4% Cu and calcination of 900 °C. Cu-N-ZrTiO4 composite can degrade MB solution up to 83% after 120 min under the irradiation of visible light.